Improvement of solubility and refolding of an anti-human epidermal growth factor receptor 2 single-chain antibody fragment inclusion bodies - Javad Salehinia; Hamid Mir Mohammad Sadeghi; Daryoush Abedi; Vajihe Akbari (Wolters Kluwer Medknow Publications, 2018)
Single chain variable fragment antibodies (scFvs) have attracted many attentions due to their small size, faster bio-distribution and better penetration in to the target tissues, and ease of expression in Escherichia coli. Although, scFv expression in E. coli usually leads to formation of inclusion bodies (IBs). The aim of this research was to improve solubilizing and refolding conditions for IBs of scFv version of pertuzumab (anti-human epidermal growth factor receptor 2 (HER2) antibody). After protein overexpression in E. coli BL21 (DE3), bacterial cells were lysed and IBs were extracted via repeated washing and centrifugation. The effect of different types, concentrations, pHs, and additive of denaturing agents on IBs solubility were evaluated. More than 40 refolding additives were screened and combinations of 10 of the best additives were check out using Plackett-Burman design to choose three refolding additives with the most positive effect on refolding of the scFv. Response surface methodology (RSM) was used to optimize the concentration of adopted additives. The most efficient buffer to solubilize IBs was a buffer containing 6 M urea with 6 mM beta mercaptoethanol, pH 11. The optimum concentration of three buffer additives for refolding of the scFv was 23 mM tricine, 0.55 mM arginine, and 14.3 mM imidazole. The bioactivity of the refolded scFv was confirmed by immunohistochemical staining of breast cancer tissue, a specific binding based method. The systematic optimization of refolding buffer developed in the present work will contribute to improve the refolding of other scFv fragments.